The Impact of the Financial Crisis to Support the Accounting Conservatism Policy: A Study in the Jordanian Industrial Corporations - & Mamo Al-qdau; Omar Ikbal (My University, 2014)
The theme of the reservation accounting is one of the oldest topics of financial accounting, which has become a prerequisite for the parties concerned with the financial report process, especially in the aftermath of the collapse witnessed by the turn of the 21st century. The research problem is summarized in the following questions: Have the financial crises affected the specific reservation accounting? Have the financial crises contributed to the accounting support reservation? And has the research aimed to identify the different interpretations of the reservation, the most important pros and cons of reservation, and find out the impact of financial crises on accounting reservation? In order to achieve the research objectives the researchers followed the descriptive approach depending on the accounting sources including Arab and foreign books, periodicals and researches, as well as designing a questionnaires which was been distributed among a study sample which included managers, financial advisors, and external and internal auditors in Jordanian shareholding companies. The study has come to a number of conclusions including: The public shareholding companies of Jordan are committed to conservative accounting in preparing the financial statements. The financial crises have led to the increased use of the reservation accounting. The financial crises have also .led to the emphasis on the specific use of the reservation accounting, and reservation accounting reduces the risk of the collapse of companies and that it is an appropriate tool to address the uncertainty faced by the accountant.

إن موضوع التحفظ المحاسبي يعد من أقدم موضوعات المحاسبة المالية وأصبح مطلبا أساسيا في الوقت الراهن من جانب الأطراف ذات العلاقة بعملية التقرير المالي خصوصا في أعقاب حالات الانهيار التي شهدها مطلع القرن الحادي والعشرين، وتلخصت مشكلة البحث في الأسئلة التالية: هل أثرت الأزمات المالية على محدد التحفظ المحاسبي؟، وهل ساهمت الأزمات المالية في دعم التحفظ المحاسبي؟، وهدف البحث إلى التعرف على التفسيرات المختلفة للتحفظ، وأهم الإيجابيات والسلبيات للتحفظ، ومعرفة أثر الأزمات المالية على التحفظ المحاسبي. وتحقيقاً لأهداف البحث قام الباحثين بإتباع المنهج الوصفي بالاعتماد على المصادر المحاسبية من الكتب والمجلات والبحوث العربية والأجنبية، فضلاً عن تصميم استمارة استبانه تم وتوزيعها على عينة الدراسة والمتمثلة بالمدراء والمستشارين الماليين ومدققي الحسابات الخارجيين والداخليين في الشركات المساهمة الأردنية. توصلت الدراسة إلى عددا من النتائج أهما: إن الشركات المساهمة العامة الأردنية تلتزم بالتحفظ المحاسبي عند إعداد القوائم المالية، وأن الأزمات المالية أدت إلى زيادة استخدام التحفظ المحاسبي وأن الأزمات المالية أدت إلى التأكيد على استخدام محدد التحفظ المحاسبي وأن التحفظ المحاسبي يخفض من مخاطر انهيار الشركات وأنه أداة مناسبة لمواجهة حالة عدم التأكد التي يتعرض لها المحاسب .
أثر الأزمات المالية على دعم سياسة التحفظ المحاسبي: دراسة في الشركات الصناعية المساهمة الأردنية